2009
DOI: 10.1007/s00253-008-1752-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of xenobiotic-degrading sphingomonads

Abstract: The genus Sphingomonas (sensu latu) belongs to the alpha-Proteobacteria and comprises strictly aerobic chemoheterotrophic bacteria that are widespread in various aquatic and terrestrial environments. The members of this genus are often isolated and studied because of their ability to degrade recalcitrant natural and anthropogenic compounds, such as (substituted) biphenyl(s) and naphthalene(s), fluorene, (substituted) phenanthrene(s), pyrene, (chlorinated) diphenylether(s), (chlorinated) furan(s), (chlorinated)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
196
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(209 citation statements)
references
References 176 publications
4
196
1
8
Order By: Relevance
“…As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013). The high abundances of NHC-degrading bacteria Brevundimonas, Sphingopyxis, Sphingosinicella Stolz 2009;Baik et al 2013), and Comamonas (Felföldi et al 2010;Zhang et al 2015) also tallied with the complete disappearance of NHCs in the final effluent in this study. The NHCutilizing bacteria detected in CWW treating sludge exhibit considerable potential for biotechnological applications.…”
Section: Discussionmentioning
confidence: 92%
“…As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013). The high abundances of NHC-degrading bacteria Brevundimonas, Sphingopyxis, Sphingosinicella Stolz 2009;Baik et al 2013), and Comamonas (Felföldi et al 2010;Zhang et al 2015) also tallied with the complete disappearance of NHCs in the final effluent in this study. The NHCutilizing bacteria detected in CWW treating sludge exhibit considerable potential for biotechnological applications.…”
Section: Discussionmentioning
confidence: 92%
“…Several genera belonging to Acetobacteraceae have been linked with hydrocarbon degradation at moderately low pH levels (Hamamura et al, 2005;Rö ling et al, 2006). Sphingomonadaceae, Burkholderiaceae and Pseudomonadaceae are recognized for their extraordinary catabolic flexibility and are among the most common hydrocarbon degraders in a variety of soils (Leys et al, 2004;Stolz, 2009;Silby et al, 2011;Pérez-Pantoja et al, 2012); however, a thorough knowledge on pH optima of these groups is still lacking. Although these results provide clues about the pH preferences of these bacterial groups in the studied site, it remains to be shown whether they successfully degrade PAH or TPH compounds under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These might be one of the reasons that why strain PHPY had substrate specificity towards PAHs different from those of strain F199 and other sphingomonads. The capability to degrade a variety of PAHs by several sphingomonads including strain F199 has been reported 37 . However, some of sphingomonads such as Sphingomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Among PAH-degrading sphingomonads, N. aromaticivorans strain F199 has been extensively studied in terms of the catabolic genes involved in hydrocarbon degradation 34 . These catabolic genes seem to be unique in phenanthrene-degrading sphingomonads 36,37 . The detection of a dioxygenase gene in strain PHPY using PCR with a primer specific for the bphA1f gene encoding the large subunit of the terminal dioxygenase of aromatic-ring-hydroxylating dioxygenase from strain F199 revealed that strain PHPY might possess catabolic genes that are not highly homologous to the genes in strain F199.…”
Section: Discussionmentioning
confidence: 99%